Using antenna arrays for reference-free measurement of speed of ultrasound and thickness of concrete articles - Kachanov, V. K.; Sokolov, I. V.; Kontsov, R. V.; Sinitsyn, A. A. (Russian journal of nondestructive testing, 2017)
A reference-free method is considered for concurrent measurement of the speed of ultrasonic vibrations and the thickness of concrete constructional products with ultrasonic antenna arrays that use the “focusing to a plane” algorithm.